SOCIAL CLASSES AND EGO IDENTITY: COMPARATIVE STUDY ON TEENAGERS AT HIGH SCHOOL - García, Juan Diego (2013)
The article offers an investigation that examines the relationship between social class condition and the characteristics of ego identity in 219 adolescents, men and women, of 16 and 17 years old, from a public and a private high school in San Jose. The methodology was quantitative, transversal and correlational with instruments of socioeconomic aspects, ego identity, self-esteem and free time. The results support the hypothesis of the incidence of social class in the configuration of subjectivity.